Pendidikan Kewarganegaraan sebagai Sarana Penguatan Wawasan Kebangsaan dalam Membangun Masyarakat yang Toleran - Dewi Romantika Tinambunan; Marly Meani Silalahi; Muthi’ah Lathifah; Al Firman; Andre Dwi Putra Sinaga; M Iqbal (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
Indonesia is a multicultural country facing serious challenges related to intolerance, social conflict, and identity polarization. This study aims to examine the strategic role of Civic Education as a means of strengthening national insight in building a tolerant society. Using a qualitative approach through literature review methods, this research analyzes various relevant sources on education, tolerance, and nationalism. The results show that Civic Education contributes to shaping students’ democratic character, inclusiveness, and appreciation of diversity. It not only transfers civic knowledge but also instills social skills and human values. However, challenges in implementation remain, such as cognitively-centered curricula and the negative influence of digital technology. Therefore, a contextual learning approach that emphasizes real-life experiences and active student participation is needed. The findings indicate the importance of synergy between schools, families, and communities in creating a conducive environment for nurturing tolerant attitudes. The implications of this research highlight the need to revitalize Civic Education as a key medium for building a peaceful, inclusive, and civilized nation amid complex social dynamics.